Implementasi bauran pemasaran informasi Bitread Publishing dalam meningkatkan jumlah terbitan buku - Ihsaninnisa, Nalurita; Rachmawati, Tine Silvana; Rodiah, Saleha (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
ABSTRACT As one of the marketing tools, the information marketing mix can not only be used in libraries, but can be applied to publishing, as a company that has the same vision, which is to increase public interest in reading. The implementation of the information marketing mix in publishing can act as a strategy in providing complete information related to what consumers need and to increase the number of book publications. The purpose of this study is to determine the implementation of the information marketing mix based on the 7Ps, namely product, price, place, promotion, people, physical evidence, and process. The method used is qualitative with a case study approach. Data collection techniques include interviews, observation, and documentation. The results obtained are (1) Bitread Publishing has implemented the information marketing mix well, (2) one of the elements of the information marketing mix that is quite developed is promotion, and what needs development is the people element, (3) positioning is found as a result of the information marketing mix at Bitread Publishing which functions to build branding, (4) positioning activities become an advantage as well as risks and consequences because they have an impact on the reduced number of book publications compared to the previous year.